Self-nano-emulsifying formulation of Sonchus oleraceus Linn for improved stability: Implications for phenolics degradation under in vitro gastro-intestinal digestion: Food grade drug delivery system for crude extract but not single compound. (February 2019) - Chen, Lei; Lin, Xiujun; Xu, Xiaowei; Chen, Yi; Li, Kang; Fan, Xiaoyun; Pang, Jie; Teng, Hui
Graphical abstract: Highlights: Phenolic compounds in Sonchus oleraceus Linn (SOL) were investigated. Self-emulsifying drug delivery system (SEMDDS) improves the stability of SOL. SEMDDS prevented extract of SOL degradation under alkaline environment. Abstract: The objective of this study was to evaluate self-emulsifying drug delivery system (SNEDDS) for phenolic-extract of Sonchus oleraceus Linn (TSF-SNEDDS). The optimal prescription of the SNEDDS was as follows: isopropyl myristate (IPM) as the oil phase, Tween-20 as the emulsifier, polyethylent glycol-400 (PEG-400) as the co-emulsifier, and the weight ratio of the three was 1:3:1 (w/w/w). The phenolic-extract loading was 11% of the prescription and it remained stable after storing at room temperature at least for 30 days without delamination. TSF-SNEDDS was found to be uniform, spherical distribution and the particle size of the emulsion was 183 ± 0.7 nm. A dynamic gastro-intestinal model was used to evaluate the behavior of TSF-SNEDDS under digestion. SNEDDS had a significant impact on stability of major phenolic compounds presented in Sonchus oleraceus Linn within the simulated gastric-intestine tract. These results indicate that SNEDDS is a promising delivery system for functional extract by increasing its stability.